Ilegalne aktivnosti u nevidljivom web-u (Kriminalističke teme, 2019)
Inspiracija za rad: Uloga hakera u vršenju ilegalnih aktivnosti pod okriljem nevidljivog dijela World Wide Web-a podstakla je autora na promišljanje o povezanosti ovih specifičnih delikvenata sa skrivenim oblastima savremene informatičke sfere.Ciljevi rada: Autor svoja razmišljanja posvećuje ustanovljavanju veze, koju hakeri sasvim moguće imaju sa potencijalnim mogućnostima okruženja Deep Web-a.Metodologija/dizajn: Analiza pojmova haker i nevidljivi Web, kroz njihovu fenomenološku uzajamnost, opredijelila je metodološki napore autora u svom istraživanju.Ograničenja rada/istraživanja: Ograničenja u prikazivanju potpune slike temeljnih pojmova u ovom radu mogu predstavljati njihovi tekući vidovi ispoljavanja, koje autor zbog tehničke nemogućnosti sagledavanja cjelokupnog varijetata njihovih pojavnih oblika nije bio u mogućnosti da predstavi.Rezultati: Veza hakera sa Deep Web-om, kako smatra autor, postoji u brojnim oblicima kriminalnih aktivnosti, od kojih će u radu biti akcentovani neki od hakerskih napada i terorizam.Generalni zaključak: Nevidljivi deo Web-a, a posebno njegova tamna zona tzv. Darknet, čine naročitu pogodnost za djelovanje hakera ante delictum, kao i post delictum, čineći istovremeno optimalno informatičko okruženje za razmjenu podataka koji vode ka pripremanju ilegalne aktivnosti, baš kao i ka kapitalizovanju štete nastale hakerskim na-padom.Opravdanost istraživanja/rada: Ukazivanjem na postojanje veze hakera sa skrivenim dijelom World Wide Weba, autor nastoji da utiče na pojačavanje opreza i unapređivanje zaštite od hakerskih napada određivanjem preventivnog postupanja, koje svaki korisnik savremene globalne komunikacije može upotrijebiti na ličnom planu u razmjeni podataka putem Interneta.Illegal Activities in the Invisible WebReason for writing and research problem (s): The very role of hackers while dealing with illegal activities within surroundings of the invisible part of the World Wide Web motivated the author to analyze relations between this special kind of offenders and hidden areas of modern informatics sphere.Aims of the paper (scientific and/or social): The author focused his attention to establishing of link that, very possible, connects hackers to the potential opportunities of the Deep Web zone.Methodology/Design: Analyze of terms hacker and invisible Web, done through their phenomenological mutuality, prevailed the author’s methodological efforts in this re-search.Research/Paper limitation: Actual forms of exposing basic terms in the paper are probable limitation to have them presented completely, because of technical lack of the author’s capability to make the full-scaled overview of their existing modalities.Results/Findings: According to the author’s opinion, the link between hacker and the Deep Web exists in the various types of criminal activities having hackers’ attacks and terrorism as highlighted in the paper.General Conclusion: Invisible part of Web and its dark zone so-called the Darknet, especially, make specific suitability for hacker’s activity ante delictum, just as post delictum, having at the same time optimal informatics surroundings enabled for the data exchanging as ground of illegal activities preparation and likewise of getting profit out of damage committed by hacker’s attack.Research/Paper Validity: By pointing out on existing of connection between hacker and hidden part of the World Wide Web, the author tends to get caution heightened and to enhance protection considering hackers’ attacks by defining preventive proceedings that can come in handy in exchanging personal data of every user of Internet global communication network.